GAMBARAN TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN PADA MASA PANDEMI COVID-19 DI PUSKESMAS AIR DINGIN KOTA PADANG - Birman, Yuliza; Antisa Larasari Deflorian; Arief Rinaldy (Nusantara Hasana Journal, 2024)
Pregnancy is one of the sources of stressors experienced by women. Every pregnant women has different level of anxiety depending on how the mother responds to her pregnancy. The level of anxiety is very influential in the welfare of the mother and the fetus in the womb, a high level of anxiety can increase complications of maternal infant mortality. The threat of Covid-19 pandemic raises anxiety in everyone without exception for pregnant women, because pregnant women are among the vulnerable groups at risk of being infected with Covid-19. Objective of this research to determine the description of the anxiety the anxiety level of third trimester pregnant women facing childbirth during the Covid-19 pandemic at Puskesmas Air Dingin Kota Padang. Methods: the scope of research is obstetrics and psychiatry. The research was conducted in January-July 2023. The type of research is descriptive obsevasional. The affordable population in the study were third trimester pregnant women who came to check pregnancy at Puskesmas Air Dingin Kota Padang, as many as 80 samples with concecutive sampling technique. Univariate data analysis is presented in form os frequency distribution and data processing using the computerized SPSS program IBM version 25.0. The most age is 20-35 years, 63 people (78.8%), the most parity is mutlipara, 33 people (40%), the most education is high school, 49 people (61,3%), most pregnant women do not work, 67 people (83,8%), and the most anxiety level is mild anxiety, 69 people (86,3%). The most age is 20-35 years, the most parity is multiparous, the mos education is high school, the most work is not working, and the most anxiety level is mild anxiety.